Anti-cancer nutraceutical composition. - Mohamed, Suhaila; Namvar, Farideh; Chan, Khee Kuang (2011)

(untitled)
A comestible composition with anti-cancer property comprises alcohol soluble extracts from plant part of Piper species, palm species, tropical seaweeds, and/or Solanum species.